Immune infertility - Korabiusz, Katarzyna; Wawryków, Agata; Stecko, Monika; Torbe, Andrzej (Journal of Education, Health and Sport, 2020)
We talk about infertility when a couple, despite regular intercourse 3-4 times a week, cannot get pregnant within a year. The problem of infertility equally affects both women and men. There are at least few reasons for this. A less common cause of infertility is immunological infertility. The paper presents the history of a couple affected by this type of infertility.